The role of tax and transfers in reducing personal income inequality in Europe's regions: Evidence from EUROMOD - Magda Mercader-Prats; Horacio Levy (University of Essex, Institute for Social and Economic Research (ISER), 2004)
In this paper we use statistical tools and graphic devices in order to give a comprehensive picture of income inequality levels in a set of 100 EU-15 regions at the end of the XX century before and after the operation of the tax-benefit. Our analysis is based on EUROMOD, the first multi-country tax-benefit model built with a common framework that includes detailed information on taxes and benefits paid and received by individuals and/or households from samples that are representative for the 15 EU countries. Our analysis focuses on intraregional inequality and it explores the relationship between regional inequality levels (both in market incomes and disposable incomes) and economic performance. Our main findings indicate that tax-benefits systems in Europe notably reduce market inequality in all EU regions and that the size of this reduction (i.e. redistributive effect) depends crucially on (i) the market inequality level of the region (positively), (ii) the relative economic performance of the region in the country (negatively) and (iii) the country to which the region belongs.
Keywords: C81; D31; I38; 330; Regions; European Union; inequality; redistribution; economic performance